Media Buku Kesehatan Ibu dan Anak Mempengaruhi Self Efficacy Ibu Hamil dalam Pemanfaatan Antenatal Care - Miranti Mandasari; Yusriani Yusriani; Sitti Patimah (FORIKES, 2021)
The Maternal and Child Health Book is one of the media used by health workers in educating pregnant women so that they can increase self-efficacy during pregnancy, childbirth and the puerperium. This study aims to analyze the influence of the MCH book media on the self-efficacy of pregnant women in the use of antenal care services at Lauwa Health Center, Gowa Regency. This type of research was a quasi experiment, with a pre post test without control group design. The sample were selected by purposive sampling method during June-July 2020 with a sample size of 35 respondents. Data were analyzed by t-test. The results showed that the MCH book media had an effect on pregnant self-efficacy in the use of antenatal care services, with a p-value